Sistem Penjualan Logam Pada PT. Semarang Jaya Makmur Dengan Metode Customer Relationship Management (CRM) - Romansyah, Alek Sergius; Amin, Fatkhul (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Customer Relationship Management (CRM) is a marketing strategy that seeks to create good relationships for provider companies with consumers and potential customers, which is expected to make consumers loyal and loyal to the company. To help prospects in the sales sector, convert them into consumers and retain pre-existing customers, satisfied and loyal consumers will lead to a relationship that lasts not only between sellers and buyers, but rather a partner relationship. Customer Relationship Management (CRM) is a method used to plan, schedule, and control activities before sales and after sales within the company. allows companies to manage budgets very well, as well as affordable sales and services. Make operational activities more efficient. The existence of this CRM method increases the service felt by consumers increased to 85% compared to before the implementation of this method, which was 55% and consumers became more satisfied and the company is also increasingly known in many other large companies.